Livro-reportagem Rotativas Silenciadas: o fim da publicação do jornal Correio de Uberlândia - Alves, Fillipe Gomes de Souza (2018)
This paper reports the non-fiction book production process Retiring the presses: the end of the publication of the newspaper Correio de Uberlândia based on research and interviews throughout the years 2017 and 2018. This work’s idea emerged three months after the closure of the activities of the only city jornal until then, a fact that brought inquiries and worries about the reasons that led to the end of a newspaper with almost 80 years old. In order to understand why to stop the publication of the vehicle and to propose answers to this problem in the format of a non-fiction book, it was necessary to go through a frame of references. Thus, we set out to produce a report divided into three conceptual chapters that present reflections about history of journalism in Brazil, such as writing a non-fiction book and memory and history concepts. The methodology used consisted of researches on the Internet and documents in Uberlândia Public Archive, specifically on printed newspapers from Uberlândia since its inception, and interviews with journalists, historiographers and people linked to the city media and the politics. All in all, 17 interviews were conducted to help with the book's narrative. With this, it was possible to bring to light several circumstances that involved Uberlândia’s press history, that we consider relevant and pertinent as hypotheses about the motivations that ledthe Correio de Uberlândia, as well as other journals before it, to the closure of its activities.